Functional Covariance Connectivity of Gray and White Matter in Olfactory-Related Brain Regions in Parkinson’s Disease - Wang, Yiqing; Wei, Hongyu; Du, Shouyun; Yan, Hongjie; Li, Xiaojing; Wu, Yijie; Zhu, Jianbing; Wang, Yi; Cai, Zenglin; Wang, Nizhuan (Frontiers in Neuroscience, 2022)
Before the onset of motor symptoms, Parkinson's disease (PD) involves dysfunction of the anterior olfactory nucleus and olfactory bulb, causing olfactory disturbance, commonly resulting in hyposmia in the early stages of PD. Accumulating evidence has shown that blood oxygen level dependent (BOLD) signals in white matter are altered by olfactory disorders and related stimuli, and the signal changes in brain white matter pathways show a certain degree of specificity, which can reflect changes of early olfactory dysfunction in Parkinson's disease. In this study, we apply the functional covariance connectivity (FCC) method to decode functional covariance connectivity of gray and white matter in olfactory-related brain regions in Parkinson's disease. Our results show that the dorsolateral prefrontal, anterior entorhinal cortex and fronto-orbital cortices in the gray matter have abnormal connectivity with the posterior corona radiata and superior corona radiata in white matter in patients with Parkinson's hyposmia. The functional covariance connection strength of the right dorsolateral prefrontal cortex and white matter, and the covariance connection strength of the left superior corona radiata and gray matter function have potential diagnostic value. These results demonstrate that alterations in functional covariance connectivity of gray and white matter in olfactory-related brain regions can reflect the change of olfactory function in the early stages of Parkinson's disease, indicating that it could be a potential neuroimaging marker for early diagnosis.